Characteristic functions for sturm—liouville problems with nonlocal boundary conditions - Štikonas, Artūras; Štikonienė, Olga (Mathematical Modelling and Analysis, 2009)
This paper presents some new results on a spectrum in a complex plane for the second order stationary differential equation with one Bitsadze‐Samarskii type nonlocal boundary condition. In this paper, we survey the characteristic function method for investigation of the spectrum of this problem. Some new results on characteristic functions are proved. Many results of this investigation are presented as graphs of characteristic functions. A definition of constant eigenvalues and the characteristic function is introduced for the Sturm‐Liouville problem with general nonlocal boundary conditions. First published online: 14 Oct 2010